OMMIP: An optimized multiple mobile agents itinerary planning for wireless sensor networks. Issue 6 (18th August 2017) - Lingaraj, K.; Biradar, Rajashree V.; Patil, V. C.
Abstract: Mobile agent is programmed software that move across networks or the among the sensor nodes. MA is capable to execute and deliver the code for efficient and re-usability of application. It performs local processing, information processing, collaborative signal. The recent research shows that the efficiency of agent based that are increases in compare to convention WSN (Wireless Sensor Network) that are performed on the client-server computation model. We discuss issues related for MA to visit the base node. In our proposal, we optimized the algorithm that based on iteratively partition in a directional sector zone, where the node will include in the method. In adaptive fashion by the Genetic algorithm schema we obtain the near optimal route. Through the angle of the direction, sector zone the length of method is controlled. The effectiveness of purposed algorithm in compare to alternative approaches will show in simulation.